(untitled) (Comprehensive Journal of Science, 2026)
The intestinal parasites and protozoan infection are amongst the most common infection worldwide .This study was conducted to investigate the prevalence of gastro-amoebiasis in children hospital, Benghazi ,over the past six years (2013 -2018). During this period , The overall prevalence was 50 cases were positive infection that recorded . The study variables included age , Gondar and demographic at diagnosis. The highest infection rate was recorded during . 2015,2016 and 2018 with rate (24.0%,) .While the lowest number of patient were showed in 2014 ( 10.0%) .At level of the month , the higher percentage was occurred during July , August and September(24.0% ) , that it was compared whit other months . The highest rate with gastro-Amoebas observed in age group ( than one years ) old ( 33) infection , compared with (17) infection in the age group (more than one years to 15 years old) . According to gender of the patient , the higher rate of prevalence was occurred in male (58.0%) than female (42.0%) . Significant regional difference were observed with in Benghazi, compared with the other regions confirmed a lower than –average prevalence . where the highest infection rate was recorded in the Benghazi (28) infection